Peran Pemeriksaan Mutasi Gen Dead-Box Helicase 41 (DDX41) pada Sindroma Mielodisplasia Hipoplastik - Budiono Raharjo; Stephani Linggawan; Anton Sumarpo; Erica Valencia Imannuel; Vegy Supriadi; Diane Lukito; Yohanes Timothy Raharjo; Wivina Riza Devi; Siprianus Ugroseno Yudho Bintoro (Majalah Kedokteran Indonesia, 2025)
Introduction: DDX41 gene mutations can occur in hematopoietic malignancies, especially acute myeloid leukemia (AML) and myelodysplastic syndrome. The average incidence of myelodysplastic syndrome (MDS) in the general population is 4.5 out of 100,000 people per year. Myelodysplastic syndrome (MDS) can occur with different genetic mutations and will provide different prognoses and therapy results. Hypoplastic myelodysplastic syndrome (MDS) is often found in 10-15% of MDS patients. There have been no case reports or research studies in Indonesia that have reported a case of hypoplastic myelodysplastic syndrome associated with a mutation in the Dead Box Helicase 41 (DDX41) gene.Case Report: A 66-year-old man presented with complaints of weakness. The patient had a history of myelodysplastic syndrome diagnosed two years earlier. Bone marrow aspiration revealed cellularity with decreased granulopoiesis and thrombopoiesis, and myeloblasts accounted for 2.0%. Genetic testing using a Next Generation Sequencing (NGS) panel identified DDX41 p.(Pro258Leu) at 47.9%, DDX41 p.(Arg525His) at 1.7%, and ASXL1 p.(Gln977Ter) at 1.6%. The patient was treated with a combination therapy of venetoclax and azacitidine. Follow-up bone marrow aspiration showed improved cellularity, increased erythropoiesis activity, and a reduction in the number of dysplastic cells. Case Discussion: Mutations in the DDX41 gene can mostly be found in cases of hypoplastic myelodysplastic syndrome, while in normocellular or hypercellular myelodysplastic syndrome, genetic mutations such as SF3B1, TET2, STAG2, ASXL1, and BCOR are mostly found. The DDX41 gene is related to cellular molecules and innate immunity. The DDX41 gene mutation is a determining factor in the administration of chemotherapy. The DDX41 gene mutation is a determining factor in the selection of chemotherapy drugs.Conclusion: DDX41 genetic testing with NGS method is essential for determining the prognosis and appropriate therapy in the management of hypoplastic myelodysplastic syndrome cases.